Pseudoxenoglossia in Mispronunciation Lyrics of The Chainsmokers Song ‘Don’t Let Me Down’ Covered by Nella Kharisma - Amalia, Annisa Nur (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Abstract This study explores the phenomenon of pseudoxenoglossia – instances where individuals produce speech resembling a foreign language without demonstrating genuine comprehension. Focusing on the performance of popular music, this research investigates how non-native speakers engage with lyrics in a foreign language, often resulting in varying degrees of accuracy and authenticity. Utilizing qualitative analysis methods, the study examines specific examples of mispronunciation and linguistic adaptation within musical performances, assessing the deviations from standard language norms and exploring the underlying causes. The theoretical framework centers on linguistic interference, which posits that a speaker's native language system exerts a significant influence on their acquisition and production of a second language. This interference can manifest in various ways, including phonological distortions, grammatical inaccuracies, and semantic misunderstandings. The analysis differentiates between instances of minor mispronunciation, where the intended meaning remains relatively clear, and more pronounced cases of pseudoxenoglossia, where utterances lack coherence and semantic content in the target language. The study identifies several contributing factors to these linguistic phenomena. Differences in phonological systems between the native language and the target language present inherent challenges in accurate pronunciation. Limited vocabulary and grammatical knowledge further contribute to errors. Additionally, sociocultural factors, such as perceptions of the audience's linguistic competence, can influence a performer's approach to linguistic accuracy. The findings highlight the complex interplay between linguistic competence, cultural context, and artistic expression in musical performance. By examining examples of linguistic adaptation and mispronunciation, this research sheds light on the ways in which foreign languages are integrated into local cultural practices. It contributes to a broader understanding of the role of popular culture in shaping linguistic attitudes and behaviors, and it underscores the importance of considering both linguistic and sociocultural factors when analyzing cross-cultural communication. This analysis gives rise to findings that illustrate how phonological interference influences non-native speakers in imitating or producing sounds in foreign languages, especially in the context of popular culture and music that is currently developing among society. The research suggests that the study has implications for language learning pedagogy and intercultural communication strategies, emphasizing the need for nuanced approaches that acknowledge the complexities of language acquisition and cultural exchange. Keywords: Pseudoxenoglossia; Linguistic Interference; Mispronunciation; Language Acquisition; Popular Culture; Cross-Cultural Communication.